Impact of Cryotherapy on Sensory, Motor, and Autonomic Neuropathy in Breast Cancer Patients Receiving Paclitaxel: A Randomized, Controlled Trial - Ng, D.Q. (Frontiers Media S.A., 2021)
10.3389/fneur.2020.604688